Pemanfaatan Aplikasi Qur’ani sebagai Media Pembelajaran Tahsin di Sekolah Menengah Atas - Marjoko Susilo (Edification Journal : Pendidikan Agama Islam, 2026)
This study aims to analyze the utilization of the Qur’ani application as an instructional medium for tahsin learning in senior high schools, focusing on three key aspects: the impact of the application on students’ reading proficiency, the challenges encountered during its implementation, and the extent to which the application is integrated into classroom instruction. A qualitative research approach was employed, with data collected through in-depth interviews, classroom observations, and supporting documentation. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the Qur’ani application significantly enhances students’ reading abilities, particularly in improving makhraj accuracy, fluency, and mastery of difficult Arabic letters. Through features such as audio examples, repeated practice, and tajweed visualization, students are able to practice independently and gain greater confidence in reading the Qur'an. Nonetheless, several challenges were identified, including limited student devices, unstable internet connections, and the lack of teacher training to utilize the application's features optimally. Pedagogical challenges also arise from varying levels of students’ initial reading abilities, which affect the uniformity of learning progress. The integration of the Qur’ani application into tahsin learning remains in its early stages; however, it demonstrates strong potential when applied systematically and consistently. Overall, the Qur’ani application contributes positively to tahsin learning and requires stronger institutional support and teacher capacity-building for effective implementation.